ANALISIS PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM DAN DAMPAKNYA TERHADAP KINERJA KEUANGAN PERUSAHAAN LQ-45 YANG TERDAFTAR DI BEI PERIODE 2007-2011 - Manurung, Amran (Jurnal Manajemen dan Bisnis, 2014)
The objective of this research was to know the influence of Financial ratio-EPS, PER, ROE, FL,DER, CR and ROA to the level of Capital and to know the effect of The serve price to the finance performance which analyzed using EVA. The sample of this research was LQ-45 which registered in Indonesia Stock Exchange from 2007 to 2011 which publicate their financial report. And the data was analyzed using double linenier analysis The result of the research shows that the financial ratio which consists of EPS, PER, ROE, FL, DER, CR and ROA simultaniously gives a significant effect to the serve price of LQ-45 in Indonesia Stock Exchange. The partial test also shows that the serve price only influenced by EPS and DER variables significantly. The level of the influence by EPS, PER, ROE, CR and ROA variables to the serve price showed after testing the determination coefficient 62.2%. Other, the result of the research also shows that the level of capital does not influences the financial performance significantly analyzed using EVA.